The Impact of Pulmonary Arterial Pressure on Exercise Capacity in Mild-to-Moderate Cystic Fibrosis: A Case Control Study - Katerina Manika; Georgia G. Pitsiou; Afroditi K. Boutou; Vassilis Tsaoussis; Nikolaos Chavouzis; Marina Antoniou; Maria Fotoulaki; Ioannis Stanopoulos; Ioannis Kioumis (Pulmonary Medicine)
Background. Pulmonary hypertension (PH) is an often complication of severe cystic fibrosis (CF); however, data on the presence and impact of pulmonary vasculopathy in adult CF patients with milder disease, is very limited. Aim. To investigate, for the first time, the impact of systolic pulmonary arterial pressure (PASP) on maximal exercise capacity in adults with mild-to-moderate cystic fibrosis, without PH at rest. Methods. This is a Case Control study. Seventeen adults with mild-to-moderate CF, without PH at rest (cases) and 10 healthy, nonsmoking, age, and height matched controls were studied. All subjects underwent maximal cardiopulmonary exercise testing and echocardiography before and within 1 minute after stopping exercise. Results. Exercise ventilation parameters were similar in the two groups; however, cases, compared to controls, had higher postexercise PASP and decreased exercise capacity, established with lower peak work rate, peak O2 uptake, anaerobic threshold, and peak O2 pulse. Furthermore, the change in PASP values before and after exercise was strongly correlated to the parameters of exercise capacity among cases but not among controls. Conclusions. CF adults with mild-to-moderate disease should be screened for the presence of pulmonary vasculopathy, since the elevation of PASP during exercise might contribute to impaired exercise capacity.